ANALISIS KEPUASAN NASABAH KOPERASI JASA KEUANGAN SYARIAH (KJKS) BAITULMAAL WA TANWIL BINA UMAT SEJAHTERA CABANG UTAMA KABUPATEN TUBAN - SETIYAWAN, ARIS (Jurnal Pendidikan Ekonomi (JUPE), 2014)
The presence of Islamic Financial Service Cooperative BaitulMaalWaTanwilBaitulUmmah Welfare Bina Main Branch felt Tuban very beneficial for the customers, members, and the public about Islamic Financial Service Cooperative BaitulMaalWaTanwilBaitulUmmah Welfare Bina Main Branch Tuban. The purpose of this study was to determine Overview of Credit Unions, and to know the benefits of Credit Unions Against Customer Satisfaction Islamic Financial Service Cooperative BaitulMaalWaTanwilBaitulUmmah Welfare Bina Main Branch Tuban.The approach in this study is quantitative, and this type of research is survey. This research was carried out on customers (members) of Islamic Financial Services Cooperative BaitulMaalWaTanwilBaitulUmmah Welfare Bina Main Branch Tuban who are customers (members) for at least one (1) year membership. And based on the results of interviews and investigations that have been carried out research on Islamic Financial Service Cooperative BaitulMaalWaBaitulTanwil (BMT) BinaUmmah Welfare Main Branch Tuban district currently has 436 customers remain, in this study using purposive sampling techniques Accidental Sampling with a total of 100 samples, in order to get better quality research and accurate.Based on the results of research and analysis and hypothesis testing, the results of this study that the Overview of Islamic Financial Service Cooperative BaitulMaalWaBaitulUmmah Welfare Development Tanwil actually been proven to have gone well and thrive to have 91 branches by 2013. Based on hypothesis testing that there are five (5) Benefits of the Credit Unions Financial Services Cooperatives Customer Satisfaction SyariahBaitulMaalWaTanwilBaitulUmmah Welfare Development , proved that meet the needs of member variables , provide convenience for the members obtain venture capital, Giving benefit members through of Business (SHU), Develop business cooperative members , and Negating the usurer practices (extortion), is really an effect on customer satisfaction and proven cooperative effect significantly. Keywords : benefits of credit unions and customer satisfaction Kehadiran Koperasi Jasa Keuangan Syariah Baitul Maal Wa Baitul Tanwil Bina Umat Sejahtera Cabang Utama Kabupaten Tuban sangat dirasakan bermanfaat bagi nasabah, anggota, dan masyarakat sekitar Koperasi Jasa Keuangan Syariah Baitul Maal Wa Baitul Tanwil Bina Umat Sejahtera Cabang Utama Kabupaten Tuban. Tujuan penelitian ini adalah untuk mengetahui Gambaran Umum Koperasi Simpan Pinjam, dan untuk mengetahui Manfaat Koperasi Simpan Pinjam Terhadap Kepuasan Nasabah Koperasi Jasa Keuangan Syariah Baitul Maal Wa Baitul Tanwil Bina Umat Sejahtera Cabang Utama Kabupaten Tuban.Pendekatan dalam penelitian ini adalah kuantitatif, dan jenis penelitian ini adalah survei. Penelitian ini dilakukan terhadap nasabah (anggota) Koperasi Jasa Keuangan Syariah Baitul Maal Wa Baitul Tanwil Bina Umat Sejahtera Cabang Utama Kabupaten Tuban yang telah menjadi nasabah (anggota) minimal selama 1 (satu) tahun keanggotaan, dalam penelitian ini menggunakan pengambilan sampel dengan teknik Purposive Accidental Sampling dengan jumlah total sebanyak 100 sampel, agar kualitas penelitian menjadi lebih baik dan akurat. Berdasarkan hasil analisis dan uji hipotesis maka hasil penelitian ini bahwa Gambaran Umum Koperasi Jasa Keuangan Syariah Baitul Maal Wa Baitul Tanwil Bina Umat Sejahtera ternyata telah terbukti telah berjalan dengan baik dan berkembang pesat hingga memiliki 91 kantor cabang pada tahun 2013. Berdasarkan pengujian hipotesis bahwa ada 5 (lima) Manfaat Koperasi Simpan Pinjam terhadap Kepuasan Nasabah Koperasi Jasa Keuangan Syariah Baitul Maal Wa Baitul Tanwil Bina Umat Sejahtera, ternyata terbukti benar-benar berpengaruh terhadap kepuasan nasabah koperasi dan terbukti berpengaruh secara signifikan. Kata kunci: manfaat koperasi simpan pinjam dan kepuasan nasabah